2011
DOI: 10.1210/jc.2011-0501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simvastatin and Metformin on Polycystic Ovary Syndrome after Six Months of Treatment

Abstract: Long-term treatment with simvastatin was superior to metformin. Improvement of ovarian hyperandrogenism continued throughout the duration of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 47 publications
2
61
1
Order By: Relevance
“…Metformin indicated considerably larger reduction in comparison with two other treatments. As the results imply, Metformin will be more useful in the patients with high FBS, whereas other studies did not show significant change in fasting glucose in the metformin[113] and simvastatin groups. [1] Therefore, the effect of metformin on FBS needs more research.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Metformin indicated considerably larger reduction in comparison with two other treatments. As the results imply, Metformin will be more useful in the patients with high FBS, whereas other studies did not show significant change in fasting glucose in the metformin[113] and simvastatin groups. [1] Therefore, the effect of metformin on FBS needs more research.…”
Section: Discussionmentioning
confidence: 85%
“…The effect of Simvastatin on TG reduction was significantly larger than two other treatments, however, in some studies metformin showed a significant effect on TG, whereas simvastanin did not. [1] In other study, TG decreased significant decrease in statin plus OC compared with OCP alone. [4] Therefore, simvastatin may be an appropriate treatment for the patients with high levels of TG.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The use of statins in PCOS might improve not only lipids but also hyperandrogenemia (87). Interestingly, it has been shown in a randomized controlled trial (RCT) in 40 PCOS patients that 12-week treatment with atorvastatin at a dose of 20 mg daily resulted in a significant increase in serum 25(OH)D concentrations that was independent of the lipid-lowering effect of atorvastatin (88).…”
Section: Womenmentioning
confidence: 99%